EFEKTIVITAS JALAN HUTAN DI SUATU PERUSAHAAN HUTAN DI RIAU - Dulsalam Dulsalam; Jurnalis Thaib (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
An investigation on the effectiveness of forest roads was conducted at PT Siak Raya Timber in Riau in 1989. The objective is to find out the information on construction and uses of forest roads. The length of main and branch roads and target and actual productions during the latest six years (from1983/1984 to 198811989) were collected. The investigation results reveal that: 1.The length of forest roads built annually by PT Siak Raya Timber ranged from 16 km (consisting of 10 km main and 6 km branch roads) to 85 km (consisting of 65 km main and 20 km branch roads), with an average of 21.66 km (consisting of 11.68 km main and 20 km branch roads). 2.The annual felling area of PT Siak Raya Timber was 2,600 ha. The road densities ranged from 6.16 m/ha to 32.69 m/ha with an average of 21.66 m/ha. The road density is some what high compared to that stated in the Forest Agreement. 3.The actual production of logs at PT Siak Raya Timber ranged from 21,225.65 m3/year to 47,199.04 m3/year with an average of 34,417.03 m3/year. 4.The differencf between target and actual production averages was relatively large i.e. 75,500 m3/year compared to 34,417.03 m3/year. The effectiveness of forest roads ranged from 268.67m3/km-year to 2,305.86 m3/km-year with an average of 1,010 m3/km-year.